A high sensing fluorescence probe to in situ study the microstructural changes of tungsten oxide nanowires induced by thermal effect - Luo, Jianyi; Huang, Jingcheng; Chen, Feng; Xu, Youxin; Zhong, Changping; Zeng, Qingguang; Tang, Xiufeng; Hu, Linshun (Applied physics letters, 2017)
In this paper, a characterization method has been developed in situ to study the microstructural changes of tungsten oxide nanowires induced by thermal effects, in which the Eu3+ rare earth ions are pre-doped into the WO3 nanowires (Eu@WO3 nanowires). The thermal effect in the Eu@WO3 nanowires have been studied by increasing the sample temperature in a nitrogen gas environment, and the results indicate the microstructural changes induced by the thermal effect could be not detected by the micro-Raman spectrum, but could be obviously detected by the fluorescence spectrum of Eu3+ fluorescence centers. The most notable effect of the increasing temperature is the appearance of two new fluorescence emissions related with a broad band emission at 675 nm and two sharp peaks at 525 and 530 nm, respectively. The understanding picture for the relationship between the new fluorescence emissions and the microstructural changes of the Eu@WO3 nanowires has also been proposed in this paper.